2023
DOI: 10.3390/su151612278
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Economy Promotes Rural Revitalization: An Empirical Analysis of Xinjiang in China

Abstract: The digital economy now plays a pivotal role in reshaping the global economic structure and optimizing the allocation of resources. With the popularization of digital technology in rural areas, the impact of the digital economy on rural development is also increasing. In order to explore the impact of the digital economy on rural revitalization in Xinjiang of China, this study constructed an indicator system based on the data from 14 prefectures or cities (of the same administrative level as the prefectures) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…To further analyze the key variables affecting the adaptation of farmers' livelihood transformation and identify the obstacle factors for improving the adaptation of farmers' livelihood transformation, existing studies have identified obstacle factors using concepts such as "factor contribution degree", "indicator deviation degree", and "obstacle degree" [46][47][48]. This research used an obstacle degree model to explore the obstacle factors of farmers' livelihood transformation adaptation.…”
Section: Quantitative Analysis Methodsmentioning
confidence: 99%
“…To further analyze the key variables affecting the adaptation of farmers' livelihood transformation and identify the obstacle factors for improving the adaptation of farmers' livelihood transformation, existing studies have identified obstacle factors using concepts such as "factor contribution degree", "indicator deviation degree", and "obstacle degree" [46][47][48]. This research used an obstacle degree model to explore the obstacle factors of farmers' livelihood transformation adaptation.…”
Section: Quantitative Analysis Methodsmentioning
confidence: 99%
“…In terms of research method, the entropy weight method (EWM) is the most popular method commonly used in the literature [14,[22][23][24][25]. Meanwhile, some scholars use the analytic hierarchy process (AHP) [26] and principal component analysis (PCA) [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Integrating digital network platforms, government and The core content revolves around promoting the sharing of rural labor [15]. With the aging population and rural "hollowing," the demand for living services is steadily increasing.…”
Section: Ensure An Amicable Living Environmentmentioning
confidence: 99%